Tocando o autêntico : os significados da autenticidade no consumo de discos de vinil - Rapeli, Marco Resende (2018)
The concept of authenticity is found in many science discussions, in which is possible to use for the human relations, objects, cultural itens, pieces of art, among others as the main object. The specific discussion about this concept applied to goods in the universe of consumption, including arts, was the main criticism of the Frankfurt School theoreticians, in the early 20th century, which had technical reproducibility and mass reproduction as the spark for studies addressing authenticity. It is essencial, therefore, that Business Administration and Marketing work with the meanings of personalization of historical goods and rescue involved in the mass context, giving or recovering value to it. Knowing that, it comes to our attention, in the contemporary background, the return of the vinyl records consumption, with seven decades of existence, as a way of consumption that allows the analysis for the historical rescue, and the quest for the authentic. This work objective is, from the concepts that define Authenticity, identify how this concept is representing the vinyl records consumption in practice, having as methodology the qualitative approach, through in-depth individual interviews with collectors, also counting on the systematic observation techniques in points of sale and netnographic observation of communities specialized in the subject in the digital environment.